Can adults learn L2 grammar after prolonged exposure under incidental conditions? - Kenanidis, Panagiotis; Dabrowska, Ewa; Llompart Garcia, Miguel; Pili-Moss, Diana (PLoS ONE, 2023)
While late second language (L2) learning is assumed to be largely explicit, there is evidence that adults are able to acquire grammar under incidental exposure conditions, and that the acquisition of this knowledge may be implicit in nature. Here, we revisit the question of whether adults can learn grammar incidentally and investigate whether word order and morphology are susceptible to incidental learning to the same degree. In experiment 1, adult English monolinguals were exposed to an artificial language (Kepidalo) that had case marking and variable word order: a canonical Subject-Object-Verb order and a non-canonical Object-Subject-Verb. In a five-session online study, participants received vocabulary training while being incidentally exposed to grammar, and completed a series of picture-selection and grammaticality judgment tasks assessing grammatical knowledge. Despite extensive exposure to input, and although performance on vocabulary increased significantly across sessions, learners’ grammatical comprehension showed little improvement over time, and this was limited to Subject-Object-Verb sentences only. Furthermore, participants were better at detecting word order than case marking violations in the grammaticality judgment tasks. Experiment 2 further increased the amount of incidental exposure whilst examining native speakers of German, which exhibits higher morphological richness. Testing was followed by a post-test metalinguistic awareness questionnaire. Although greater learning effects were observed, participants continued to have difficulties with case marking. The findings also demonstrated that language outcomes were modulated by learners’ level of metalinguistic awareness. Taken together, the results of the two experiments underscore adult learners’ difficulty with case marking and point towards the presence of a threshold in incidental L2 grammar learning, which appears to be tightly linked to prior first language experience. In addition, our findings continue to highlight the facilitative role of conscious awareness on L2 outcomes.
CRIS-Team Scopus Importer:2023-08-11

Cue reliability, salience and early comprehension of agreement: Evidence from Greek - Kenanidis, Panagiotis; Chondrogianni, Vicky; Legendre, Géraldine; Culbertson, Jennifer (Journal of Child Language, 2020)
Previous studies across languages (English, Spanish, French) have argued that perceptual salience and cue reliability can explain cross-linguistic differences in early comprehension of verbal agreement. Here we tested this hypothesis further by investigating early comprehension in Greek, where markers have high salience and reliability (compared to Spanish and English) predicting early comprehension, as in French. We investigated two and three-year-old Greek-speaking children’s ability to distinguish third person singular and plural agreement in a picture-selection task. We also examined the frequency of these morphemes in child-directed speech to address input effects. Results showed that three-year-olds are sensitive to both singular and plural agreement, earlier than children acquiring English and Spanish, but later than French, and despite singular agreement being more frequent than plural agreement in the child corpus. These findings provide further support for the role of salience and reliability during early acquisition, while highlighting a potential effect of morpheme position.
CRIS-Team Scopus Importer:2020-11-06
Keywords: Cue reliability; Greek; Language comprehension; Perceptual salience; Verbal agreement

Redundancy can hinder adult L2 grammar learning: evidence from case markers of varying salience levels - Kenanidis, Panagiotis; Llompart, Miquel; Fernández Santos, Sara; Dabrowska, Ewa (Frontiers in Psychology, 2024)
Grammatical redundancy is a widespread feature across languages. Although redundant cues can be seen to increase the complexity and processing burden of structures, it has been suggested that they can assist language acquisition. Here, we explored if this learning benefit can be observed from the very initial stages of second language (L2) acquisition and whether the effect of redundancy is modulated by the perceptual salience of the redundant linguistic cues. Across two experiments, three groups of adult native speakers of English were incidentally exposed to three different artificial languages; one that had a fixed word order, Verb-Object-Subject, and two in which thematic role assignment was additionally determined by a low-salient (Experiment 1) or a high-salient (Experiment 2) redundant case marker. While all groups managed to learn the novel language, our results pointed towards a hindering role of redundancy, with participants in the non-redundant condition achieving greater learning outcomes compared to those in both redundant conditions. Results also revealed that this impeding effect of redundancy on L2 learners can be attenuated by the salience of the redundant cue (Experiment 2). In conjunction with earlier findings, the present results suggest that the effect of redundancy on L2 acquisition can be differentially manifested depending on the stage of L2 development, learners’ first language biases and age.
CRIS-Team Scopus Importer:2024-06-14
Keywords: artificial language learning; grammar; redundancy; salience; second language acquisition